Antiviral properties of antineoplastic drugs. From Herpes simplex-1disappearance to a wide antiviral action: a serendipity case report - Debernardis, A.; Alfonsi, G.; Santacroce, L.; Bottalico, et al., L. (Acta Biomedica Atenei Parmensis, 2009)
Herein we report the clinical case of a 46 year old female affected by lung cancer and cerebral metastases who showed, one month after the beginning of an oncologic therapy with vinorelbine and cisplatin, the complete remission of periodic (every 15 days) recurrences of herpetic mouth lesions. More than one year after the disappearance of the herpetic lesions, no further evidence of them were found. Subsequently, specific laboratory investigations, together with another case report that is presently in process, showed that vinorelbine, aside from its well known antineoplastic properties, also exerts a powerful antiviral action.